Drinking, Drug Use, and Related Consequences Among University Students Completing Study Abroad Experiences: A Systematic Review. (5th December 2016) - Aresi, Giovanni; Moore, Simon; Marta, Elena
ABSTRACT: Background : University students who complete study abroad experiences are potentially exposed to behaviors, in particular alcohol and drug use, that place their health at risk. There is a need to identify risk and protective factors and highlight knowledge gaps. Methods : A systematic review adopting the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. Relevant bibliographic databases and online repositories were systematically searched for both qualitative and quantitative peer-reviewed studies. Results : Eighteen articles were eligible for inclusion. Degree mobility students (DMSs—students pursuing a full bachelor or master degree in a foreign country) and Credit Mobility Students (CMSs—students participating in short term or semester study abroad programmes) show different patterns of at-risk behaviors compared to pre-departure, and to domestic or non-study abroad students. DMSs mostly consumed less alcohol and illicit substances compared to domestic students, but little information on pre-travel behavior and predictors of at-risk behaviors while abroad was available on DMSs. Most studies indicated that CMSs increased their alcohol use while abroad and reduced it when they returned home. However, there is no evidence of an increase in the negative consequences associated with alcohol misuse while abroad. Different pre-departure and abroad factors (e.g., perceptions of peer drinking norms, psychological and sociocultural adjustment abroad) were related to at-risk behaviors in the host country. Conclusions : University students who study abroad are understudied and potentially at risk from alcohol and drug use. Knowledge gaps are discussed in relation to possible future qualitative, mixed methods and longitudinal research.